PRIVACY MANAGEMENT AND THE CULTURE OF OVERSHARING ON SOCIAL MEDIA: A PHENOMENOLOGICAL STUDY OF GRADUATE STUDENTS IN COMMUNICATION STUDIES - Didang Sri Erkata Silalahi; Eka Widya Lestary; Masharoh Ulfah Rajali (OPINI: Journal of Communication and Social Science, 2025)
Social media has blurred the boundaries between private and public life, creating new challenges for privacy management among communication students. This study explores how graduate students in communication understand privacy, perceive the impacts of oversharing, and negotiate boundaries in their social media use. Using a qualitative phenomenological approach, the research involved in-depth interviews with six graduate students, analyzed through source triangulation and guided by theories of privacy meaning, Communication Privacy Management (CPM), boundary regulation, uses and gratifications, and digital well-being. The findings show that students perceive privacy management not only as data protection but also as a psychological and emotional safeguard. They employ strategies such as maintaining multiple accounts, audience segmentation, deliberate identity construction, and regulating posting frequency. Oversharing fulfills self-expression needs but also generates digital anxiety, social pressure, and concerns over digital footprints. While communication theory enhances reflective awareness, it does not fully counteract the influence of an open digital culture. Overall, privacy management emerges as an ongoing reflective process essential to digital well-being and ethical communication.